(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The problem of excess or deficiency of nutrients in adolescents will increase susceptibility to disease, especially the occurrence of non-communicable diseases such as hypertension, diabetes, coronary heart disease, stroke, and cancer, if not addressed immediately. Limiting eating and drinking that contain high levels of sugar, salt, and fat is a preventive measure for non-communicable diseases in adolescents. The purpose of community service is to increase adolescents’ knowledge about preventing and overcoming nutritional problems. The community service method is to provide training to 100 adolescents of SMAN 1 Banyuwangi through material presentation and practice on adolescent health and nutrition issues, adolescent nutrition problems and how to overcome them, and how to choose healthy food and drinks according to adolescent needs with the Health Heroes Nutrihunt application. The analysis used to determine the results of the training is the pre-test and post-test. The results of this service show that there is an increase in adolescents’ knowledge about the topic of exposure, as seen from the results of the pre-test and post-test, which have an average of 46.23 and 72.96, respectively, which shows an increase of 57.8% and can be seen from the enthusiasm to practice identifying types of packaged food and drinks that are good for consumption. With this training, adolescents in schools are able to sort and choose foods and drinks before consumption based on their nutritional content.